PENDAMPINGAN KELOMPOK PKK DALAM PENGOLAHAN KRIPIK RUMPUT LAUT CRISPY DI DESA SUKAJADI, KECAMATAN CARITA, KABUPATEN PANDEGLANG - Wahyiah, Ita Rosita; Pratiwi, Diah Ayu; Akbarudin; Sam, Maulana Suprihatin; Rendiyani, M; Ina Sabrina, Ina; Aulia, Dita; Sefriyandi, Andi; Agustina, Anggi Ratna; Vinoza, Veranica Febrilla (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Sukajadi Village, Carita Sub-district, Pandeglang Regency, has great potential in the development of processed seaweed products. With the availability of abundant raw materials and high public interest in local processed products, the development of crispy seaweed chips can be one of the community's economic empowerment efforts. The PKK group as one of the active community organisations in the village has an important role in this effort. Through proper assistance, PKK groups can increase production capacity, produce quality products, and develop sustainable businesses. Objectives of Assistance Improving knowledge and skills Improving the PKK group's knowledge of seaweed processing techniques into quality crispy chips. Assist PKK groups to produce crispy seaweed chips with good flavour, crunchy texture, and attractive appearance.